Analysis of the external region of the Pluto system for different values of inclination and eccentricity of the particles - Winter, Silvia M. Giuliatti [UNESP]; Gallardo, Daniel G. [UNESP] (My University, 2017)
Pluto and Charon form a binary system due to the large mass ratio (μ = 0.12) and the small distance (d = 19570km) between them. Four small satellites, discovered after the launch of the New Horizons spacecraft, are located exterior to Charon's orbit. Styx, Nix, Kerberos and Hydra have very small eccentricity and are all coplanar with Charon's orbital plane. In this work we analysed the external region for a set of particles with different values of eccentricity and inclination. From our numerical simulations, taking into account the gravitational effects of Pluto and its five satellites, we generate diagrams of a versus e and a versus I after a timespan of 105 orbital periods of Charon (about 650000days). The external region was divided into three: a) region 1 between 1.5d to 2.5d - Styx and Nix are located in this region; b) region 2 between 2.5d to 3.5d - Kerberos and Hydra are located in this region, and c) region 3 external to Hydra's orbit. For values of I > 0 most of the particles at region 1 escape the system due to the gravitational effects of Charon, while in region 2 the particles suffer small variation in the values of e and I, specially those particles trapped in mean motion resonance. Region 3, as expected, is a stable region. When the effects of the solar radiation pressure is included in the system, most of the particles, regardless its size and orbital inclination, are ejected or collide with the massive bodies in a very short period of time.
Keywords: Kuiper belt object; Numerical simulations; Stable regions